2020
DOI: 10.3390/molecules25092121
|View full text |Cite
|
Sign up to set email alerts
|

All-Solid-State Lithium Ion Batteries Using Self-Organized TiO2 Nanotubes Grown from Ti-6Al-4V Alloy

Abstract: All-solid-state batteries were fabricated by assembling a layer of self-organized TiO2 nanotubes grown on as anode, a thin-film of polymer as an electrolyte and separator, and a layer of composite LiFePO4 as a cathode. The synthesis of self-organized TiO2 NTs from Ti-6Al-4V alloy was carried out via one-step electrochemical anodization in a fluoride ethylene glycol containing electrolytes. The electrodeposition of the polymer electrolyte onto anatase TiO2 NTs was performed by cyclic voltammetry. The anodized T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 43 publications
0
17
0
Order By: Relevance
“…The most explored anodic oxide in batteries devices is recently based on TiO 2 applied as anodes in ion batteries to overcome the technical issues during lithiation/delithiation cycling [ 137 , 138 , 139 ]. The major reports are devoted to LIBs [ 27 , 32 , 56 , 140 , 141 ] and sodium-ion batteries (SIBs) [ 28 , 142 , 143 ]. These studies reported the use of nanotubes or nanoporous TiO 2 in pristine form, or doped (with Al, V, Nb, N, S), or in composites (with TiN, SnO 2 , CNT, CuO, CoO, Co 3 O 4 ).…”
Section: Energy Storage Devices: Supercapacitors and Batteriesmentioning
confidence: 99%
See 4 more Smart Citations
“…The most explored anodic oxide in batteries devices is recently based on TiO 2 applied as anodes in ion batteries to overcome the technical issues during lithiation/delithiation cycling [ 137 , 138 , 139 ]. The major reports are devoted to LIBs [ 27 , 32 , 56 , 140 , 141 ] and sodium-ion batteries (SIBs) [ 28 , 142 , 143 ]. These studies reported the use of nanotubes or nanoporous TiO 2 in pristine form, or doped (with Al, V, Nb, N, S), or in composites (with TiN, SnO 2 , CNT, CuO, CoO, Co 3 O 4 ).…”
Section: Energy Storage Devices: Supercapacitors and Batteriesmentioning
confidence: 99%
“…The search for alternative materials to replace conventional electrodes in LIBs and SIBs aimed to improve kinetic processes and storage capacity [ 59 , 144 ] and extend the device’s life cycle [ 145 , 146 ]. With a theoretical capacity of 330 mAh·g −1 and a good cycle life [ 140 ], the use of nanostructured anodic TiO 2 in LIBs is also stimulated by the low volume change (≈4%) during the reversible intercalation of lithium ions into its structure [ 56 , 83 , 140 , 144 ]. The Li + ions insertion from the cathode into the TiO 2 anode proceed as follows [ 140 ]: TiO 2 + xLi + + xe − → Li x TiO 2 …”
Section: Energy Storage Devices: Supercapacitors and Batteriesmentioning
confidence: 99%
See 3 more Smart Citations